Renta extractiva y la minería del cobre en el Perú - Landa Arroyo, Yuri Jesús (2017)
In the framework of a weak approach to sustainability, this paper evaluates whether the revenues earned on copper mining have translated into better educational, health, and roadway infrastructure in Peru’s extractive zones, both at the district- and department wide level, between 2004 and 2013. The results reveal that the infrastructure in places that are home to the extractive industries has indeed improved to a greater degree than in other locations, but only on a small order of magnitude. This weak effect is tied to the State’s shaky vision of sustainability and the fact that the regionalization process in Peru is still under way.